2015
DOI: 10.3390/s151026801
|View full text |Cite
|
Sign up to set email alerts
|

Measurement Properties of the Smartphone-Based B-B Score in Current Shoulder Pathologies

Abstract: This study is aimed at the determination of the measurement properties of the shoulder function B-B Score measured with a smartphone. This score measures the symmetry between sides of a power-related metric for two selected movements, with 100% representing perfect symmetry. Twenty healthy participants, 20 patients with rotator cuff conditions, 23 with fractures, 22 with capsulitis, and 23 with shoulder instabilities were measured twice across a six-month interval using the B-B Score and shoulder function ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
2
5
0
Order By: Relevance
“…They presented with one of the following shoulder conditions, as recorded during their first medical consultation at the specialized shoulder consultation unit of the hospital: rotator cuff condition, adhesive capsulitis, proximal humerus fracture i.e. the pathologies for which the B-B score measurement properties were known as appropriate [ 29 ]. With the exception of patients with fracture, patients who gave their consent underwent the measurement session within two weeks following medical consultation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They presented with one of the following shoulder conditions, as recorded during their first medical consultation at the specialized shoulder consultation unit of the hospital: rotator cuff condition, adhesive capsulitis, proximal humerus fracture i.e. the pathologies for which the B-B score measurement properties were known as appropriate [ 29 ]. With the exception of patients with fracture, patients who gave their consent underwent the measurement session within two weeks following medical consultation.…”
Section: Methodsmentioning
confidence: 99%
“…The smartphone was also attached to the back of the arm with an armband. The lower edge of the smartphone was set 3 cm above the upper edge of the inertial sensors’ module [ 29 ]. Similar to previous work angular velocities and accelerations in the sensor frame have been used to calculate the B-B Score [ 11 , 28 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This has enabled Wireless Body Area Networks (WBANs)/Wireless Body Sensor Networks (WBSNs) to become a key technology in real-time health monitoring of patients, providing effective detection and treatment of acute diseases [1,2,3,4,5,6,7]. It is envisioned that WBAN/WBSN will have an annual device shipment of 187.2 million units by 2020 [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Apps rely on an internal smartphone inclinometer 26 or a photographic virtual goniometer 21 to measure ROM. Several studies have demonstrated joint ROM measured with apps to be reliable and accurate compared with traditional methods,7, 14, 15, 19, 21, 23, 25, 26, 29 but studies performed on the shoulder were limited by inclusion of only participants with no joint disease (for whom they have the most potential clinical application). In addition, no shoulder study considered the impact that ROM variability may have on shoulder scores with an objective ROM component.…”
mentioning
confidence: 99%